Anemia, Diet, and Cognitive Development: Impact of Health Information on Diet Quality and Child Nutrition in Rural India - Marion Krämer; Santosh Kumar; Sebastian Vollmer (Institute of Labor Economics (IZA), 2021)
Lack of information about health risks may limit the adoption of improved nutritional and healthy behavior. This paper studies the effect of a nutrition information intervention on household dietary behavior, hemoglobin levels, and cognitive outcomes of children in rural India. Using experimental data and regression discontinuity design that exploits the exogenous cutoff of hemoglobin level for anemia, we find statistically insignificant treatment effects on dietary improvements, child health, and cognitive outcomes of children. Our findings suggest that light-touch nutrition information alone, even when parents are informed about the health risk of their children, may not promote healthy behavior and factors other than information might constrain households in making nutritional investments for their children.
Keywords: 330; health information; child health; anemia; cognition; regression discontinuity; India